Biological Chemistry (De Gruyter, 1878)
Biological Chemistry keeps you up-to-date with the latest advances in the molecular life sciences. The journal publishes Research Articles, Short Communications, Reviews and Minireviews. Areas include: general biochemistry/pathobiochemistry, structural biology, molecular and cellular biology, genetics and epigenetics, virology, molecular medicine, plant molecular biology/biochemistry and novel experimental methodologies.